Global assessment of chemical quality of drinking water: The case of trihalomethanes. (15th February 2023) - Villanueva, Cristina M; Evlampidou, Iro; Ibrahim, Fathelrahman; Donat-Vargas, Carolina; Valentin, Antonia; Tugulea, Anca-Maria; Echigo, Shinya; Jovanovic, Dragana; Lebedev, Albert T; Lemus-Pérez, Mildred; Rodriguez-Susa, Manuel; Luzati, Arben; et al.
Highlights: First international assessment on THM regulations, routine monitoring, and occurrence. Many low- and middle-income countries still do not regulate THMs in drinking water. 47% of countries with THM regulations do not conduct routine monitoring. Large variability in THM data availability and population coverage among countries. Efforts needed to regulate, monitor, and assess chemical quality of drinking water worldwide. Abstract: Background: Trihalomethanes (THM), a major class of disinfection by-products, are widespread and are associated with adverse health effects. We conducted a global evaluation of current THM regulations and concentrations in drinking water. Methods: We included 120 countries (∼7000 million inhabitants in 2016), representing 94% of the world population. We searched for country regulations and THM routine monitoring data using a questionnaire addressed to referent contacts. Scientific and gray literature was reviewed where contacts were not identified or declined participation. We obtained or estimated annual average THM concentrations, weighted to the population served when possible. Results: Drinking water regulations were ascertained for 116/120 (97%) countries, with 89/116 (77%) including THM regulations. Routine monitoring was implemented in 47/89 (53%) of countries with THM regulations. THM data with a varying population coverage was obtained for 69/120 (58%) countries consisting of ∼5600 million inhabitants (76% of world's population in 2016). Population coverage was ≥90% in 14 countries, mostly in the Global North, 50–89% in 19 countries, 11–49% among 21 countries, and ≤10% in 14 countries including India, China, Russian Federation and Nigeria (40% of world's population). Discussion: An enormous gap exists in THM regulatory status, routine monitoring practice, reporting and data availability among countries, especially between high- vs. low- and middle-income countries (LMICs). More efforts are warranted to regulate and systematically assess chemical quality of drinking water, centralize, harmonize, and openly report data, particularly in LMICs. Graphical abstract: Image, graphical abstract